Novel Pt(II) and Pd(II) complexes with polyamine analogues: Synthesis and vibrational analysis - Silva, T.M. (2012)
A vibrational spectroscopy study (infrared and Raman) is reported for the biogenic polyamine analogues norspermidine (NSpd), N(1),N(11)-bis(ethyl)norspermine (BENSpm) and N(1)-cyclo-propylmethyl-N(11)-ethylnorspermine (CPENSpm), as well as for their newly synthesised Pt(II) and Pd(II) complexes. Attending to the potential antineoplastic properties of this kind of systems, their full conformational characterization is essential for understanding the molecular basis of their cytotoxic activity and the mechanisms through which they are transported into the cell. The all-trans geometry was found to be favoured for all the alkylated polyamines, in their totally protonated state, while their polynuclear complexes presented a stable geometry very similar to that previously obtained for the analogous chelates with spermidine (M(3)Spd(2)) and spermine (M(2)Spm), comprising two or three cisplatin-like (MCl(2)NH(2)) moieties.